ANALISIS FAKTOR YANG MEMPENGARUHI MANAJEMEN PAJAK DENGAN INDIKATOR TARIF PAJAK EFEKTIF PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2012-2015 - Islahatul Wafiroh, 12.05.52.0022; Kartika, Andi (Students' Journal of Accounting and Banking, 2016)
This research to analyze of factors affect the tax management with indicators of effective tax rate on company listed in Indonesia Stock Exchange for years 2012-2015. This research was conducted in Indonesia Stock Exchange with purposive sampling method with the sampel was taken from the period of 2012-2015.  The sample collected includes 236 companies which satisfied some criteria. Analysis tool used multiple regression analysis. The result revealed that profitability and investor instiutional has negative effect and significant to effective tax rate. Other results revealed that the inventory intensity has positive effect and significant to effective tax rate. Whereas the firm size, leverage, fixed asset intensity, and tax facilities had no significant effect on effective tax rate.  Keywords: Tax Management, Effective Tax Rate, Firm Size, Leverage, Profitabilty, Fixed Asset Intensity, Inventory Intensity, Investor Institutional, Tax Facilities